Non-coding RNAs in Cardiac Regeneration - Yuan, Ting; Krishnan, Jaya (Frontiers in Physiology, 2021)
The adult heart has a limited capacity to replace or regenerate damaged cardiac tissue following severe myocardial injury. Thus, therapies facilitating the induction of cardiac regeneration holds great promise for the treatment of end-stage heart failure, and for pathologies invoking severe cardiac dysfunction as a result of cardiomyocyte death. Recently, a number of studies have demonstrated that cardiac regeneration can be achieved through modulation and/or reprogramming of cardiomyocyte proliferation, differentiation, and survival signaling. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), are reported to play critical roles in regulating key aspects of cardiomyocyte physiologic and pathologic signaling, including the regulation of cardiac regeneration both in vitro and in vivo. In this review, we will explore and detail the current understanding of ncRNA function in cardiac regeneration, and highlight established and novel strategies for the treatment of heart failure through modulation of ncRNAs-driven cardiac regeneration.